Biodegradative Capability of Molecularly Identified Pseudomonas fluorescens Strains on Palm Oil-Polluted Soil - Bukola Margaret Popoola; Ayooluwa Afelumo; Oyindamola John Samson (Darul Yasin Al Sys, 2026)
Oil palm (Elaeis guineensis) is an important source of edible vegetable oil derived from the fruit mesocarp; however, oil extraction commonly generates wastewater and residues that may be discharged into the environment without adequate treatment. Because microorganisms can degrade organic contaminants in palm oil mill effluent and oil-contaminated matrices, this study aimed to evaluate the potential of Pseudomonas fluorescens for remediating palm oil-contaminated soil. Palm oil and P. fluorescens isolates were obtained from Fiditi Oil Mill and Ajayi Crowther University, respectively, in Oyo State, Nigeria. Uncontaminated soil, oil mill soil, and purposefully contaminated soil were used as experimental control samples, while four purposefully contaminated soil samples and four oil mill soil samples were treated with P. fluorescens under varying soil sterilization and tillage conditions. The isolate was identified using 16S rRNA gene sequence analysis, and a 12-week field bioremediation trial was conducted to assess microbial load and residual oil content. The 16S rRNA sequencing confirmed the isolate as P. fluorescens MN607218.1. Residual oil in tilled sterile purposefully contaminated soil decreased from 0.13 g on day 0 to 0.10 g by week 12, whereas the corresponding non-sterile soil showed a greater reduction to 0.07 g by week 12. These findings indicate that P. fluorescens can effectively degrade palm oil in contaminated soil, particularly under non-sterile conditions, and may serve as a promising microbial agent for environmental cleanup of palm oil-contaminated sites.